Development of Student Worksheets on the Inquiry-Flipped Classroom Model on Addictive and Addictive Substance Material to Improve Student's Argumentation Abilities - Epinur Epinur; Minarni Minarni (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to develop worksheets by following the syntax of the inquiry-flipped classroom learning model to improve argumentation skills on addictive and addictive substances, using the ADDIE development model (analysis, design, development, implementation, and evaluation). Research data was obtained by distributing questionnaires to validation design and material experts, teachers, and student responses. The results of this study were that the first percentage was 80% (valid) and the second validation was 92% (very valid), the first stage learning design validation was 87.5% (valid), and the second validation was 93.75% (very valid). Limited trials were carried out on teachers and students. They obtained practical criteria with a percentage of 90% and student responses of 84.68%, so it is feasible to use in learning. The developed student’s worksheet can improve students' argumentation skills at level 1 by 13%, level 2 by 16%, level 3 by 25%, level 4 by 28%, and level 5 by 19%.